Oxidative Stress and Antioxidant Capacity in Different Species of Limpets - González, Paula Mariela (2013)
Limpets are gastropod molluscs that inhabit intertidal rocky shores. Due to the localization of these animals, they are exposed to a wide variety of environmental stressors: tidal immersion/emersion cycles, sharp salinity variations, extreme temperature effects, solar and UV radiation and anthropogenic influences. It was suggested that antioxidant systems may be altered after exposure to these stressors. The aim of this work is to summarize oxidative disruption related to environmental stress in limpets from different geographical areas, comparing the available information on antioxidant defenses (enzymatic activities, content of water and lipid soluble antioxidants), as well as lipid damage content. To further characterize the complex interaction between oxygen and nitrogen reactive species, the more recent reports on the presence of NO in limpets will be shown and discussed.